Asas Filosofi Teori Belajar Essensialisme dan Implikasinya dalam Pendidikan - Abas, Erjati (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2015)
Essentialism is a conservative educational philosophy which was originally formulated as a critique on progressive trends in schools. They argue that the progressive movement has undermined the standards of intellectual and moral among young people. Education must on the basic of the values that can bring stability to have a value system that is clear and has been tested by time. Essentialism principle requires that education is the foundation of the essential values and nature walks. Essentialism philosophical view about the study should be done with great effort, because the success of the learning activities carried out by someone because of a continuing effort without despair and stopped, because the essentialist view a persons success does not just arise in students. Asa philosophical principles of learning theory essentialism is the implication in the learning activities will alter the function of the school, the purpose of learning, the curriculum, the learning process, the role of educators and learners.